2011
DOI: 10.1128/jvi.00535-11
|View full text |Cite
|
Sign up to set email alerts
|

Mx Is Dispensable for Interferon-Mediated Resistance of Chicken Cells against Influenza A Virus

Abstract: Finally, we found that both isoforms of chicken Mx protein appear to lack GTPase activity, which might explain the observed lack of antiviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 45 publications
0
49
1
Order By: Relevance
“…One speculative possibility is that homologs of MxA in other hosts have selected for some level of generalized MxA resistance in all NPs. Determining whether this is the case will require characterizing whether MxA homologs of the relevant species do in fact exert selection on influenza virus: there is evidence that swine MxA restricts influenza [48, 49], but the anti-influenza activity of avian MxA remains incompletely characterized across most bird species that are hosts for influenza [5052]. Even if other MxA homologs exert selection, we would not expect non-human viruses to be optimally resistant to human MxA since MxA homologs have different specificities [53].…”
Section: Discussionmentioning
confidence: 99%
“…One speculative possibility is that homologs of MxA in other hosts have selected for some level of generalized MxA resistance in all NPs. Determining whether this is the case will require characterizing whether MxA homologs of the relevant species do in fact exert selection on influenza virus: there is evidence that swine MxA restricts influenza [48, 49], but the anti-influenza activity of avian MxA remains incompletely characterized across most bird species that are hosts for influenza [5052]. Even if other MxA homologs exert selection, we would not expect non-human viruses to be optimally resistant to human MxA since MxA homologs have different specificities [53].…”
Section: Discussionmentioning
confidence: 99%
“…RT was performed using Revertaid (Fermentas) with oligo(dT) (for measuring chMx and chIL28RA mRNA) or random hexamers (for measuring viral RNA) with 1 g of DNase-treated RNA in a final volume of 20 l. One microliter of RT product was used for qPCR analysis using the Sensifast SybrHi-Rox kit (Bioline, Luckenwalde, Germany) according to the manufacturer's instructions. Primers for influenza A virus detection were derived from Fouchier et al (24), and primers for chMx mRNA amplification were derived from Schusser et al (25). Primers qPCRmbRA-F (5=-GAAGCCG GATCTGAAGACAA-3=) and qPCRmbRA-R (5=-TGATATCTTAAC ACATCCTTCCTCAG-3=) were used for detecting chIL28RA mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…In analogy to the mammalian system the avian Mx orthologue was considered to have potent antiviral properties [25, 26]. Surprisingly, in vitro and in vivo studies clearly demonstrated that chicken Mx does not limit influenza virus replication despite strong induction of the protein by IFN [27, 28]. Thus, it remains to be elucidated which IRGs confer antiviral resistance in different viral disease.…”
Section: Introductionmentioning
confidence: 99%